Quantitative or qualitative carbon dioxide monitoring for manual ventilation: a mannequin study. (3rd February 2015) - Hawkes, GA; Kenosi, M; Ryan, CA; Dempsey, EM
Abstract: Aim: To compare the effectiveness of an in‐line EtCO2 detector (DET) and a quantitative EtCO2 detector (CAP), both attached to a t‐piece resuscitator, during PPV via a face mask. Methods: Paediatric trainees were randomly assigned to determine the method of PPV they commenced with (No device (ND), DET or CAP). Participants used each method for 2 min. Participants were video‐recorded to determine the amount of effective ventilations delivered with each method. Results: Twenty‐three paediatric trainees provided a total of 6035 ventilations, and 91.2% were deemed effective. The percentages of median effective ventilations with the ND, the DET and the CAP were 91.0%, 93.0% and 94.0%, respectively. Fourteen (61%) of the trainees indicated a preference for the DET method, 8 (35%) for the CAP method, and 1 (4%) of the trainees indicated a preference for the ND method. Capnography was the most effective method per patient. Conclusion: There was no adverse effect with the addition of EtCO2 detectors. Trainees favoured methods of EtCO2 monitoring during ventilation. The NeoStat device was the preferred device by the majority. The greatest efficacy was achieved with the capnography device. Capnography may enhance face mask ventilation.